Is the effect of exchange rate volatility on trade more pronounced in Latin America than in Asia? - Dieter Billen; Maria Melody Garcia; Nelli Khasanova (Kiel Institute for World Economics (IfW), 2005)
This paper empirically investigates the impact of exchange rate volatility on East and Southeast Asian and Latin American exports from 1980 to 2004 by using a gravity model and panel data. The results show that exchange rate volatility negatively affects exports in both continents. However, the impact of exchange rate volatility is more pronounced in Latin America than in Asia for the whole sample period 1980-2004 and in the sub-period 1980-1996, but not in the sub-period 1997-2004. Moreover, the results also show that countries with relatively high tariffs are less vulnerable to exchange rate volatility than open economies. Finally, evidence reveals that exports from high-income countries are less affected by exchange rate volatility.
Keywords: 330